hey... i was going over my midterm.. studying for the final today at 6. i came up to this question and couldnt reduce it... Z = ( B' + C + D' )( A' + B' + C' )( B + C' + D ) PLEASE HELP thanx
Z=(A'B'+B'B'+B'C'+A'C+B'C+C'C'+A'D'+B'D'+C'D')(B+C'+D) Z=(A'B'+B'+B'C'+A'C+B'C+C'+A'D'+B'D'+C'D')(B+C'+D) Z=(B'(A'+1+C'+C+D')+A'C+C'(1+D')+A'D')(B+C'+D) Z=(B'+A'C+C'+A'D')(B+C'+D) A'C+C'=A'+C' Z=(B'+A'+C'+A'D')(B+C'+D) Z=(B'+A'(1+D')+C')(B+C'+D) Z=(B'+A'+C')(B+C'+D) Z=BB'+B'C'+B'D+A'B+A'C'+A'D+BC'+CC'+C'D Z=B'C'+B'D+A'B+A'C'+A'D+BC'+C'D Z=C'(B'+B+A')+D(B'+C')+A'B Z=C'+B'D+C'D+A'B Z=C'(1+D)+B'D+A'B Z=C'+B'D+A'B